Zigzag and zeitgeist: motivation in organizations. Issue 5 (3rd September 2018) - Apter, Michael J.; Desselles, Mitzi
Abstract : Purpose: The purpose of this paper is to introduce an unconventional approach to personality and motivation, known as reversal theory, and to bring out some of its challenging practical implications, especially for organizations. The theory emphasizes frequent change and people's tendency to "zigzag" creatively through life rather than be limited by fixed traits, or types, which limit their capabilities. Design/methodology/approach: The paper introduces some basic concepts of the reversal theory. Findings: Research shows, among other things, that there are four basic pairs of motivational states that people reverse between in the course of everyday life, that individuals vary in terms of their degree of "motivational intelligence", and that organizations have contrasting emotional "microclimates" that can be controlled and changed by leaders as needs change. Research limitations/implications: The theory has been developed from some 40 years of dedicated psychological research – observational, clinical, psychometric, and experimental – in many different countries and on a wide variety of topics. Practical implications: The psychological theory was developed originally from work in clinical and counseling psychology and has always had an applied orientation. Practical concepts touched on in this paper include motivational intelligence, psychological reversal, and microclimates. These ideas have been applied in many different fields including personal and leadership development, workplace satisfaction, and customer relations. Originality/value: The theory clearly contrasts with other psychological theories, has empirical support, and has proved itself in various applied contexts.